2004
DOI: 10.1007/bf03184727
|View full text |Cite
|
Sign up to set email alerts
|

Aeroacoustic characteristics and noise reduction of a centrifugal fan for a vacuum cleaner

Abstract: The aero acoustic characteristics of a centrifugal fan for a vacuum cleaner and its noise reduction method are studied in this paper. The major noise source of a vacuum cleaner is the centrifugal fan. The impeller of the fan rotates at over 30000 rpm, and generates very high-level noise. It was revealed that the dominant noise source is the aerodynamic interaction between the rotating impeller and stationary diffuser. The directivity of acoustic pressure showed that most of the noise propagates backward direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Jeon et al (2003Jeon et al ( , 2004 identified the acoustic characteristics of a centrifugal fan and suggested an impeller design to reduce the tonal noise. They showed experimentally that the overall noise level and the strong tonal noise produced from a vacuum cleaner are reduced by a tapered impeller design.…”
Section: Introductionmentioning
confidence: 99%
“…Jeon et al (2003Jeon et al ( , 2004 identified the acoustic characteristics of a centrifugal fan and suggested an impeller design to reduce the tonal noise. They showed experimentally that the overall noise level and the strong tonal noise produced from a vacuum cleaner are reduced by a tapered impeller design.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, product manufacturers focused on reducing noise levels produced by the suction units. However, they reached a point where further noise level reduction is hard to achieve or at least not financially feasible [1]. On the other hand, researchers investigated the perceptual aspects of vacuum cleaner sounds and showed that the sound power levels of the products are not sufficient to characterize the users' perception of the product sound (e.g., [2][3][4]).…”
Section: Introductionmentioning
confidence: 99%
“…One of the important review is given by Neise which summarized all the efforts to reduce passage tone noise by improving the geometry of the impeller and its cut off [2]. Jeon et al [3] published the method to reduce tonal noise of centrifugal fan by application of tapered impeller and uneven pitched impeller. Yilmaz et al [4] presented the method on numerical noise prediction of a radial fan.…”
Section: Introductionmentioning
confidence: 99%